RESILIENT MODULUS PROPERTIES OF MINE OVERBURDEN TREATED WITH FLY ASH-BASED GEOPOLYMER - Nagendra Mondem; Dharma R.B; Umashankar Balunaini (GEOMATE Journal, 2025)
Due to the global need for mineral resources and the large increase in population, mining activity has increased significantly. The growing need for sustainable growth in the mining industry highlights the importance of waste management throughout the whole mining process. The main objective of the study is to utilize the mine overburden (OB) soil in pavement subgrade applications. According to the mechanistic empirical pavement design guidelines, the fundamental input parameters include the resilient modulus (MR) characteristics of the pavement layers. Mine OB soil typically exhibits relatively low resilient modulus and strength properties. The addition of fly ash (FA) based geopolymer additive is one of the solutions to enhance these properties. This study examines the effect of the addition of 0% to 50% fly ash-based geopolymer to mine OB soil that was sourced from open-pit coal mines in the State of Telangana, India. An alkaline activator solution consisting of sodium hydroxide with 3M concentration and sodium silicate mixed in a ratio of 1.0 is used. The cyclic triaxial tests are conducted as per AASHTO T-307-99 to determine the resilient modulus model as a function of deviator and radial stresses. The addition of fly ash-based geopolymer to mine OB soil significantly increased the resilient modulus. From the results, the study identified the 70OB:30FA mixture as the optimal mixture.